THE FACILITIES AND ACTIVITIES TANGKAHAN PT. PUTRA BEROMBANG PERKASA ATBELAWANFISHING PORTNORTH SUMATERA PROVINCE - Frandihka Guru Singa; Bustari Bustari; Ronald M. Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted on 8-20 May 2018 in Tangkahan PT. Putra Berombang Perkasaat Belawan Fishing Port. The purpose of this study was to determine the facilities and activities of PT. Putra Berombang Perkasa at Belawan Ocean Fishing Port. The method used in this research the survey method. Data analysis was carried out descriptively in the form in tables or image forms. Based on research that the Tangkahan facility has various facilities commonly used to support fisheries activities.Facilities available at Tangkahan PT. Putra Berombang Perkasa consists of basic facilities (land, docks, shipping lanes, plaster, port roads), functional facilities (delivery/TPI, sorting and writing tables, scales, carts, ice grinding machines, workshops, fishing gear storage areas, and places storage of lubricants/oil), and supporting or additional facilities consist of (Tangkahan administration office, guard post, canteen, and parking area). While the activities in Tangkahan are landing activities of catches, replenishment of fishing supplies, mooring of ships, marketing of fishing products, and repairs/maintenance of shipsKey words: Facilities, Aktivities, Tangkahan, BelawanFishing Port